Socio-economic Impact of Flue-Cured Tobacco in Northern Light Soils Zone of Andhra Pradesh (Indian Journal of Extension Education, 2018)
The present study attempts to assess the impact of FCV (Flue Cured Virginia) tobacco crop on socio-economic transformation of tobacco farmers in NLS (Northern Light Soils) zone of Andhra Pradesh. A total of 10 villages were selected by purposive sampling representing progressive tobacco growing villages and non-tobacco growing villages. Twelve farmers were randomly selected from each village so that 60 tobacco and 60 non-tobacco farmers represented the total sample of the study. Tobacco is adequately financed by the banks to an average extent of up to ` 72,000/acre in addition to inputs supplied by Tobacco Board, whereas for other selected crops, the average scale of finance restricted to a maximum limit of ` 30,000/acre. The average net returns per acre of own land is higher for tobacco (` 49,806) than other selected crops grown in the region. The socio-economic impact analysis revealed that tobacco farmers are comparatively having well-furnished houses (38.34%), possession of vehicles like two wheelers (96.66%), four wheelers (31.66%), tractors (28.33%), more number of livestock with 5-10 animals (20%), more than one bore well for farm irrigation (11.66%), access to refrigerators (61.66%) in addition to televisions (100%), having bank accounts (100%) and also, access to overseas higher education (11.67%) than non-tobacco growers. The total labour employed per acre for tobacco (131) is comparatively higher than paddy (31), maize (40) and sugarcane (52) including mechanization.